Pengaruh Cooperatif Learning Tipe Think Pair Share (TPS) Berbasis Potensi Lokal terhadap Hasil Belajar Mahasiswa - Nurhidayati, Siti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The aim of this research is to describe the influence of cooperative learning type Think Pair Share (TPS) based on local potential on student learning outcomes in professional teaching courses. This type of research is descriptive research with a qualitative approach. The sample for this research was students from the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education, which programs professional teaching courses. This research instrument is in the form of student learning outcomes questions consisting of 6 questions in essay form. Data on student learning outcomes were analyzed descriptively. The results of the descriptive analysis show that the average pre-test score reached 67, increasing to 89 in the post-test, so it can be concluded that there is an influence of the Think Pair Share (TPS) learning model on student learning outcomes.